ANALISIS YURIDIS PENERBITAN SURAT PERINTAH PENGHENTIAN PENYIDIKAN (SP3) YANG DIKELUARKAN KEPOLISIAN DALAM KASUS PELECEHAN SEKSUAL TERHADAP ANAK - Harahap, Chairunnazri; Yunara, Edi; Marlina, Marlina (Smart Education, 2025)
Abstract:The process is still carried out the same as other criminal cases, except that at each stage of the examination there is a companion who always accompanies child victims of sexual violence in each examination. Legal regulations related to the issuance of a letter of order to stop the investigation by the Indonesian National Police are regulated in Article 109 Paragraph 2 of the Criminal Procedure Code and Article 30 of Perkap Number 6 of 2019 concerning Investigation. Legal protection for victims of sexual harassment if a letter of order to stop the investigation is issued by the Indonesian National Police is always provided by the Medan Police, but there are a number of obstacles, both from the number of personnel which is still limited and Coordination with the Medan City PPA UPTD. Keyword:Child, Sexual Harassment, Medan Police Abstrak: Proses tetap dilakukan sama dengan perkara pidana lainnya, hanya saja dalam setiap tahapan pemeriksaan terdapat pendamping yang senantiasi selalu mendamping anak korban kekerasan seksual dalam setiap pemeriksaan. Pengaturanhukumterkaitpenerbitan surat perintahpenghentianpenyidikanolehKepolisian Republik Indonesia diatur di dalamPasal 109 Ayat 2 KUHAP danPasal 30 PerkapNomor 6 tahun 2019 TentangPenyidikan. Perlindunganhukumterhadapkorbantindakpidanapelecehanseksualapabiladiterbitkan surat perintahpenghentianpenyidikanolehKepolisian Republik Indonesia selaludiberikanolehPolrestabes Medan namun hal ini terdapatsejumlahkendalabaik dari jumlahpersonil yang masihterbatasdanKoordinasidengan UPTD PPA Kota Medan. Kata kunci: Anak, PelecehanSeksual, Polrestabes Medan